Selective Affimers Recognise the BCL‐2 Family Proteins BCL‐xL and MCL‐1 through Noncanonical Structural Motifs. (2nd November 2020) - Miles, Jennifer A.; Hobor, Fruzsina; Trinh, Chi H.; Taylor, James; Tiede, Christian; Rowell, Philip R.; Jackson, Brian R.; Nadat, Fatima A.; Ramsahye, Pallavi; Kyle, Hannah F.; Wicky, Basile I. M.; Clarke, Jane; et al.
Abstract: Abstract : The BCL‐2 family is a challenging group of proteins to target selectively due to sequence and structural homologies across the family. Selective ligands for the BCL‐2 family regulators of apoptosis are useful as probes to understand cell biology and apoptotic signalling pathways, and as starting points for inhibitor design. We have used phage display to isolate Affimer reagents (non‐antibody‐binding proteins based on a conserved scaffold) to identify ligands for MCL‐1, BCL‐xL, BCL‐2, BAK and BAX, then used multiple biophysical characterisation methods to probe the interactions. We established that purified Affimers elicit selective recognition of their target BCL‐2 protein. For anti‐apoptotic targets BCL‐xL and MCL‐1, competitive inhibition of their canonical protein‐protein interactions is demonstrated. Co‐crystal structures reveal an unprecedented mode of molecular recognition; where a BH3 helix is normally bound, flexible loops from the Affimer dock into the BH3 binding cleft. Moreover, the Affimers induce a change in the target proteins towards a desirable drug‐bound‐like conformation. These proof‐of‐concept studies indicate that Affimers could be used as alternative templates to inspire the design of selective BCL‐2 family modulators and more generally other protein‐protein interaction inhibitors. Abstract : Affimer reagents (non‐antibody binding proteins) are identified that bind selectively to the anti‐apoptotic proteins BCL‐xL and MCL‐1. Crystallographic studies reveal an unprecedented mode of molecular recognition in which flexible loops from the Affimer dock into the BH3 binding cleft as opposed to a canonical α‐helix. Furthermore the Affimers induce changes in the target proteins towards desirable drug‐bound‐like conformations.